HUBUNGAN CARA MENERAN DENGAN KEJADIAN RUPTUR PERINEUM PADA IBU BERSALIN DALAM PERSALINAN KALA II DI PMB DESA SUKASARI KECAMATAN RUMPIN KABUPATEN BOGOR - Widianingsih, Fitri; Tridiyawati, Feva (Jurnal Ilmiah Global Education, 2023)
A tear of the birth canal becomes the second cause of postpartum hemorrhage. Technique straning can affect the occurrence of perineal rupture in mothers who give birth spontaneously. The biggest cause of maternal death is bleeding, which is 30.3% and old partus is the lowest cause at 1.8%, but better treatment is needed so that it does not occur during labor (Ministry of Health, 2018). This study aims to analyze how to straining with incidence of perineal rupture in maternity mothers in Kala II Labor at PMB Sukasari Village, Rumpin District, Bogor Regency. The research method used is an observational analytical with a cross sectional approach. The population in this study was 55 people with a sample of 35 primiparous mothers. This research instrument uses SOP observation sheets for how to run and partograph sheets. Data processing is carried out univariately and bivariately with Chi Square Test with the help of SPSS computer program. The results of the study indicate that there is a relationship how to straining the Valsalva technique and the perineal rupture whith a volue ρ = 0.004 < α = 0.005 indicating that how to straining the valsava technique affects the incidence of perineal rupture. The results of the study concluded that the way of straining can affect the incidence of perineal rupture at the time of labor. It is recommended that pregnant women in the third trimester can learn to straining properly so that there is no perineal rupture at the time of delivery